Medidas de acurácia dos indicadores clínicos do diagnóstico de enfermagem dinâmica alimentar ineficaz do adolescente da rede pública de ensino - Sousa, Tamires Mesquita (2020)
Eating behaviors and habits among adolescents have been changing over the past few years due to socioeconomic, cultural and psychological factors. Because of this change, an inadequate dietary pattern is establishing itself associated with altered dietary dynamics. Ineffective adolescent eating dynamics is a diagnosis recently included in the NANDA-I taxonomy that requires studies to improve its level of evidence. Based on this, the aim of this study is to ascertain the measures of accuracy of the clinical indicators of the nursing diagnosis of Ineffective adolescent eating dynamics in the public school system. It is a cross-sectional study on diagnostic accuracy that was carried out in 10 public high schools in Fortaleza. The population was composed of students who met the criterion of being regularly enrolled in a high school in Fortaleza. Adolescents with chronic non-communicable diseases that could hinder the diagnostic inference were excluded from the study. The sample size was 630 adolescents selected by applying a conglomerate sample. The study was approved by the Ethics and Research Committee of the Federal University of Ceará and by the consent of the Secretary of Education of Ceará. To obtain the information, the following instruments were built: a clinical protocol with the conceptual and operational definitions of clinical indicators and a data collection instrument. Accuracy measures were calculated using latent class analysis. There was a predominance of females with a median age of 17 years. Most adolescents were eutrophic. The prevalence of Ineffective adolescent eating dynamics was estimated at 42.4% by latent class analysis, with the following most frequent clinical indicators: Undereating; Avoids participation in regular mealtimes; Frequently eating processed foods; Overeating; and Complaints of hunger between meals. After adjusting the latent class model, the clinical indicators that obtained high sensitivity values were: Frequently eating processed foods, Overeating and Undereating. Frequently eating poor-quality food and Frequent snacking food frequently presented themselves as indicators with high specificity values. Frequently eating processed foods and Overeating were present in all sets of indicators for which the probability for the diagnosis to be present was greater than 50%. Moreover, among the seven indicators with the best measures of accuracy, Frequently eating processed foods, Overeating and were presented as the most important for the inference of Ineffective adolescent eating dynamics. In addition to enabling a better diagnostic reasoning process, the identification of accurate indicators can contribute to the refinement of a diagnosis, with an improvement in its level of evidence.